Hydrogel fracture experiment: from different stimuli to delayed fracture study (B) - Ng, Julius Yi Qin (Nanyang Technological University, 2023)
Hydrogels are 3D network structures that can absorb considerable amount of water without dissolving due to cross-links or chain entanglements. They can exist naturally, such as in collagen, which is a form of polymer, or can be made synthetically. To be classified as a hydrogel, water must make up at least 10% of the total volume.